Novel dye-sensitized solar cell architecture using TiO2-coated Ag nanowires array as photoanode - Wang, Ming (2021)
With the aim of reducing series resistance and increasing dye loading, novel dye-sensitized solar cell architecture was designed with TiO2 nanoparticle-coated Ag nanowires array as the photoanode. Ag nanowire array was prepared by anodic aluminum oxide (AAO) template-assisted electrochemical deposition route. Then, Ag nanowires were coated by TiO2 nanoparticles in hydrothermal process. The structures of the photoanode were characterized by field emission scanning electron microscopy (FESEM). Ag nanowires are covered by a layer of very fine nanoparticles with a diameter of less than 5 nm. X-ray diffraction (XRD) and selected-area electron diffraction (SAED) show that Ag nanowires have a strong preferred orientation in (220) direction and the TiO2 coating layer is a polycrystalline structure. With this photoanode, 3.2 % conversion efficiency is achieved for the cell sensitized with N3 dye.